The Role of Red Blood Cell Distribution Width for Predicting 1-year Mortality in Patients Admitted to the Emergency Department with Severe Dyspnoea - Turcato, Gianni (J Med Biochem, 2017)
BACKGROUND: Universally accepted and validated instruments for predicting the outcome of patients presenting to the emergency department (ED) with severe dyspnoea do not exist so far, nor are they regularly used by the emergency physicians. This study hence aimed to establish whether red blood cell distribution width (RDW) may be a predictive parameter of 1-year mortality in a population of patients admitted to the ED with severe dyspnoea attributable to different underlying disorders. METHODS: We retrospectively evaluated all the patients undergoing arterial blood gas analysis for severe dyspnoea (irrespective of the cause) during admission to ED of University Hospital of Verona from September 1, 2014 to November 31, 2014. RESULTS: The final study population consisted of 287 patients for whom complete clinical and laboratory information was available. Overall, 36 patients (12.5%) died after a 1-year follow-up. The RDW value was found to be considerably increased in patients who deceased during the follow-up compared to those who survived (17.2% versus 14.8%; p<0.001). In both univariate and multivariate analyses, the RDW value was found to be a significant predictor of 1-year mortality. In particular, patients with RDW ≥ 15.0% displayed a 72% increased risk of 1-year mortality after multiple adjustments. CONCLUSIONS: The measurement of RDW, a very simple and inexpensive laboratory parameter, may represent an important factor for predicting medium-term mortality in patients presenting to the ED with severe dyspnoea.